Numerical modeling of laser cooling in molecules: From simple diatomics to polyatomics and radioactive species - Felix Kogel; Tatsam Garg; Phillip Groß; Lukas Leczek; Marian Rockenhäuser; Neil Shah; Jakob Weiß; Andreas Schindewolf; Tim Langen (Computer Physics Communications, 2026)

Pheromone-based mating disruption suppresses cigarette beetle (Lasioderma serricorne) trap captures in a large tobacco processing facility - Peter A. Edde; Jessica Lindenmayer; Tim Reid; Thomas W. Phillips (Journal of Stored Products Research, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Nitrate contamination in New Zealand's domestic drinking water with a focus on rural groundwater-sourced self-supplies - Karyne M. Rogers; Diane Bradshaw; Phil Scadden; Conny Tschritter; Stuart Sanderson; Jannine Cooper; Andy Phillips; Jennifer Pannell; Juliane Thern; Steve Abel; Michael K. Joy; Xing Liu; et al. (Science of The Total Environment, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Climate Benefits of Saltmarsh Restoration Greatly Overstated by Mason et al. (2023) - Phillip Williamson; Robert W. Schlegel; Jean‐Pierre Gattuso; Julian E. Andrews; Tim D. Jickells (Global Change Biology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Regional invasion history and land use shape the prevalence of non‐native species in local assemblages - Daijun Liu; Franz Essl; Bernd Lenzner; Dietmar Moser; Philipp Semenchuk; Tim M. Blackburn; Phillip Cassey; Dino Biancolini; César Capinha; Wayne Dawson; Ellie E. Dyer; Benoit Guénard; et al. (Global Change Biology, 2024)
The ecological impact of non‐native species arises from their establishment in local assemblages. However, the rates of non‐native spread in new regions and their determinants have not been comprehensively studied. Here, we combined global databases documenting the occurrence of non‐native species and residence of non‐native birds, mammals, and vascular plants at regional and local scales to describe how the likelihood of non‐native occurrence and their proportion in local assemblages relate with their residence time and levels of human usage in different ecosystems. Our findings reveal that local non‐native occurrence generally increases with residence time. Colonization is most rapid in croplands and urban areas, while it is slower and variable in natural or semi‐natural ecosystems. Notably, non‐native occurrence continues to rise even 200 years after introduction, especially for birds and vascular plants, and in other land‐use types rather than croplands and urban areas. The impact of residence time on non‐native proportions is significant only for mammals. We conclude that the continental exchange of biotas requires considerable time for effects to manifest at the local scale across taxa and land‐use types. The unpredictability of future impacts, implied by the slow spread of non‐native species, strengthens the call for stronger regulations on the exchange of non‐native species to reduce the long‐lasting invasion debt looming on ecosystems' future.

Island hydrogeology in the tropics: Constraining a 3D variable-density groundwater flow and solute transport model with geophysics - Eddie W. Banks; Saskia Noorduijn; Vincent E.A. Post; Tim Munday; Camilla Sorensen; Kevin Cahill; Phillip Jolly; Joanna Ellis; Adrian D. Werner; Okke Batelaan (Journal of Hydrology, 2024)

Feasibility of Microlearning for Improving the Self-Efficacy of Cancer Patients Managing Side Effects of Chemotherapy - Anna Janssen; Kavisha Shah; Melanie Rabbets; Adnan Nagrial; Christopher Pene; Clare Zachulski; Jane L. Phillips; Paul Harnett; Tim Shaw (Journal of Cancer Education, 2023)
Lung cancer patients have a high symptom burden that negatively affects their quality of life. Increasing patient self-efficacy to deal with treatment side effects can ameliorate their symptom burden. Education programs can help enhance patient self-efficacy by giving patients more control over their condition through increased disease literacy. This study aimed to evaluate the feasibility of microlearning for delivering lung cancer patients’ information on side effects of chemotherapy. Secondary objectives of the program are to understand the acceptability of microlearning for delivery this type of education to lung cancer patients and the potential impact of microlearning on patient self-efficacy, knowledge and confidence managing side effects of chemotherapy. A mixed-methods prepost test (or quasi-experimental) study design was used to better enable patients to identify and manage the side effects of their condition and chemotherapy. Participants were patients diagnosed with stage II to stage IV lung cancer, who had a life expectancy of greater than 3 months and were aged 18 years or older. Multiple validated scales were used to assess patient self-efficacy pre- and post-intervention. The online program was evaluated using quantitative data of completion rates extracted from the online platform. Semi-structured interviews were used to explore the impact of the online program on perceived self-efficacy and quality of life. Twenty-three participants agreed to participate in the study and five agreed to complete a semi-structured interview. Participants found the content comprehensive, relevant and engaging. The program improved perceived disease literacy and helped participants develop coping strategies to manage side effects. Participants also found the platform easy to use and navigate. Additional courses and features were requested. Patients with a diagnosis of cancer receive a large amount of information about the side effects of chemotherapy and how to manage them. This information is often provided soon after diagnosis or upon commencement of therapy, which can be overwhelming for some patients. Microlearning, a method of online learning that spaces distributing of content over several weeks, may be a useful tool for supporting delivering of health information to this group of patients.

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

DAMA: the global Distribution of Alien Mammals database - Dino Biancolini; Vittorio Vascellari; Beatrice Melone; Tim M. Blackburn; Phillip Cassey; Sally L. Scrivens; Carlo Rondinini (Ecology, 2021)
We developed the DAMA (Distribution of Alien Mammals) database, a comprehensive source reporting the global distribution of the 230 species of mammals that have established self‐sustaining and free‐ranging populations outside their native range due to direct or indirect human action. Every alien range is accompanied by information on its invasion stage, pathway, method of introduction, and date of introduction. We collected information from 827 different sources (scientific literature, books, risk assessments, reports, online biodiversity databases and websites), and used it to draw alien range maps for these species following the IUCN mapping framework. DAMA comprises 2,726 range polygons, covering 199 countries, 2,190 level 1 administrative areas, and 11 zoogeographic realms for the period 21500 BC–AD 2017. The most represented orders among introduced mammal species are Rodentia ( n = 58, 25.22%), Cetartiodactyla ( n = 49 species, 21.30%), Carnivora ( n = 30 species, 13.04%), Diprotodontia ( n = 28, 12.17%), and Primates ( n = 26, 11.30%). Mammal species have been frequently introduced for hunting ( n = 100), pet trade ( n = 57), conservation ( n = 51), and fauna improvement ( n = 42). The majority of range polygons are placed on islands ( n = 2,196, 80.56%), encompass populations that have moved beyond establishment and into the invasion stage ( n = 1,655, 60.71%), and originated from 1500 AD to the present ( n = 1,496, 54.88%). Despite inheriting literature biases towards more studied regions (e.g., developed countries), DAMA is the most up‐to‐date picture of alien mammal global distribution and can be used to investigate their invasion ecology across different biogeographical regions. There are no copyright or proprietary restrictions; IUCN range maps were modified into a derivative work according to the IUCN’s terms of service.

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

Evolution of salmon lice in response to management strategies: a review - Andrew Coates; Ben L. Phillips; Samantha Bui; Frode Oppedal; Nick A. Robinson; Tim Dempster (Reviews in Aquaculture, 2021)
Ectoparasitic salmon lice ( Lepeophtheirus salmonis ) present a major challenge to Atlantic salmon ( Salmo salar ) aquaculture. The demand for effective louse control has produced diverse management strategies. These strategies essentially impose novel selection pressures on parasite populations, driving the evolution of resistance. Here we assess the potential for salmon lice to adapt to current prevention and control methods. Lice have evolved resistance to at least four of five chemical therapeutants, and use of these chemicals has declined significantly in recent years. The industry has shifted to alternative non‐chemical approaches, yet lice may adapt to these as well. Early research suggests that phenotypic variation exists in the louse population upon which non‐chemical selection pressures could act and that this variation may have a genetic basis. From the existing evidence, as well as an examination of evolutionary processes in other relevant parasite and pest systems, we conclude that the evolution of non‐chemical resistance is an emergent concern that must be considered by the industry. We recommend areas for focused research to better assess this risk. It is also important to determine whether phenotypic shifts in response to non‐chemical selection may shift the ecological niche of the parasite, as this may have cascading effects on wild salmon populations. We also recommend further research to identify strategy combinations that have antagonistic selective effects that slow louse evolution and those with synergistic effects that should be avoided. Greater understanding of evolutionary processes can inform aquaculture policies that counteract the rise of resistant parasite populations.

Long-term inter- and intraspecific dietary variation in sibling seabird species - William F. Mills; Tim I. Morley; Stephen C. Votier; Richard A. Phillips (Marine Biology, 2021)

Invasion costs, impacts, and human agency: response to Sagoff 2020 - Ross N. Cuthbert; Sven Bacher; Tim M. Blackburn; Elizabeta Briski; Christophe Diagne; Jaimie T. A. Dick; Franz Essl; Piero Genovesi; Phillip J. Haubrock; Guillaume Latombe; Bernd Lenzner; Yves Meinard; et al. (Conservation Biology, 2020)
Article impact statement : In an era of profound biodiversity crisis, invasion costs, invader impacts, and human agency should not be dismissed.

Evidence for Rapoport’s rule and latitudinal patterns in the global distribution and diversity of alien bird species - Ellie E. Dyer; David W. Redding; Phillip Cassey; Ben Collen; Tim M. Blackburn (Journal of Biogeography, 2020)
Aim To quantify global latitudinal patterns in the distributions of alien bird species to assess whether these species conform to Rapoport's rule (i.e. show a positive latitudinal gradient in latitudinal range extent), and to test whether where species are introduced, and where species fail to establish, may help to drive observed patterns. Location Global. Taxon Birds (group Aves). Methods Data on locations of introduction and establishment for 355 species with established alien populations were combined with data on native range extents (measured in 5° bands of latitude). Relationships between (a) latitude and introduced and established alien species richness, and (b) latitude and introduced and established alien range extent, were plotted. Linear regressions and paired t ‐tests were used to compare latitudinal range extents, midpoints, and limits of each species in its introduced alien range, established alien range and native range. Results Latitudes that have more established alien bird species also have had more species introduced in total. The mean total latitudinal extents (i.e. geographic range size) of established alien bird species increase with latitude poleward of the tropics, consistent with Rapoport's rule, but are smaller in the tropics. This pattern is weaker in the range sizes of native bird species. Alien bird species are more likely to be introduced within the latitudinal confines of their native ranges, and are more likely to contract away from the more extreme latitudes to which they were introduced. Alien bird species are in general more likely to have established populations nearer the equator. Main conclusions Including data on locations of introduction in addition to established distributions enables us to determine the extent to which large‐scale alien species distributions are determined by anthropogenic or natural processes. Latitudinal patterns in range extent (Rapoport's rule) and species richness in alien birds are largely a consequence of where species have been introduced, and hence are unlikely to be informative of equivalent patterns in native species.

Colonization pressure: a second null model for invasion biology - Tim M. Blackburn; Phillip Cassey; Richard P. Duncan (Biological Invasions, 2020)
Understanding the causes of spatial variation in the distribution and richness of alien species is a key goal of invasion biology. Thanks to the increasing availability of geographical compendia of alien species it is also the subject of a burgeoning scientific literature. Here, we review elements of this literature to argue that understanding the causes of variation in alien species richness cannot be achieved without knowledge of the number of species introduced to an area—termed colonization pressure. The implications of a lack of information on colonization pressure are widespread and, we believe, poorly recognised. We start by discussing a recent general model for alien species richness that demonstrates why colonization pressure is a fundamental determinant of this. We then explore the literature on alien species richness, particularly on islands, to demonstrate how failing to account for colonization pressure affects our perception of richness drivers. We further show that ignoring colonization pressure can bias our understanding of patterns in the distributions of alien species. We finish by discussing situations when colonization pressure may be more or less important for our understanding of alien invasions.

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

A general model for alien species richness - Richard P. Duncan; Phillip Cassey; Alex L. Pigot; Tim M. Blackburn (Biological Invasions, 2019)

Species Matter: Wood Density Influences Tropical Forest Biomass at Multiple Scales - Oliver L. Phillips; Martin J. P. Sullivan; Tim R. Baker; Abel Monteagudo Mendoza; Percy Núñez Vargas; Rodolfo Vásquez (Surveys in Geophysics, 2019)

Ground Data are Essential for Biomass Remote Sensing Missions - Jérôme Chave; Stuart J. Davies; Oliver L. Phillips; Simon L. Lewis; Plinio Sist; Dmitry Schepaschenko; John Armston; Tim R. Baker; David Coomes; Mathias Disney; Laura Duncanson; Bruno Hérault; et al. (Surveys in Geophysics, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Conventional land‐use intensification reduces species richness and increases production: A global meta‐analysis - Michael Beckmann; Katharina Gerstner; Morodoluwa Akin‐Fajiye; Silvia Ceaușu; Stephan Kambach; Nicole L. Kinlock; Helen R. P. Phillips; Willem Verhagen; Jessica Gurevitch; Stefan Klotz; Tim Newbold; Peter H. Verburg; et al. (Global Change Biology, 2019)
Most current research on land‐use intensification addresses its potential to either threaten biodiversity or to boost agricultural production. However, little is known about the simultaneous effects of intensification on biodiversity and yield. To determine the responses of species richness and yield to conventional intensification, we conducted a global meta‐analysis synthesizing 115 studies which collected data for both variables at the same locations. We extracted 449 cases that cover a variety of areas used for agricultural (crops, fodder) and silvicultural (wood) production. We found that, across all production systems and species groups, conventional intensification is successful in increasing yield (grand mean + 20.3%), but it also results in a loss of species richness (−8.9%). However, analysis of sub‐groups revealed inconsistent results. For example, small intensification steps within low intensity systems did not affect yield or species richness. Within high‐intensity systems species losses were non‐significant but yield gains were substantial (+15.2%). Conventional intensification within medium intensity systems revealed the highest yield increase (+84.9%) and showed the largest loss in species richness (−22.9%). Production systems differed in their magnitude of richness response, with insignificant changes in silvicultural systems and substantial losses in crop systems (−21.2%). In addition, this meta‐analysis identifies a lack of studies that collect robust biodiversity (i.e. beyond species richness) and yield data at the same sites and that provide quantitative information on land‐use intensity. Our findings suggest that, in many cases, conventional land‐use intensification drives a trade‐off between species richness and production. However, species richness losses were often not significantly different from zero, suggesting even conventional intensification can result in yield increases without coming at the expense of biodiversity loss. These results should guide future research to close existing research gaps and to understand the circumstances required to achieve such win‐win or win‐no‐harm situations in conventional agriculture.

Water use efficiency, photosynthesis and plant growth of Chia (Salvia hispanica L.): a glasshouse experiment - Stella Lovelli; Maria Valerio; Tim D. Phillips; Mariana Amato (Acta Physiologiae Plantarum, 2019)

Species invasions and the phylogenetic signal in geographical range size - Alex L. Pigot; Ellie E. Dyer; David W. Redding; Phillip Cassey; Gavin H. Thomas; Tim M. Blackburn (Global Ecology and Biogeography, 2018)
Aim Accelerating rates of anthropogenic introductions are leading to a dramatic restructuring of species distributions globally. However, the extent to which invasions alter the imprint of evolutionary history in species geographical ranges remains unclear. Here, we provide a global assessment of how the introduction, establishment and spread of alien species alters the phylogenetic signal in geographical range size using birds as a model system. Location Global. Time period Contemporaneous. Taxa Birds. Methods We compare the phylogenetic signal in alien range size with that of native distributions of species globally ( n = 9,993) and across different stages in the invasion pathway, from introduced ( n = 965) to established species ( n = 359). Using stochastic simulations, we test whether differences in phylogenetic signal arise from nonrandom patterns of species introduction, establishment or spread. Results Geographical range size in birds exhibits an intermediate phylogenetic signal, driven by the spatial clustering of closely related species. Nonrandom introductions, biased towards wide‐ranging species from particular clades and regions, produce an anomalously strong phylogenetic signal in the native range size of introduced species. In contrast, the phylogenetic signal in alien range size is substantially weaker than for native distributions. This weak phylogenetic signal cannot be explained by a lack of time for dispersal but is instead regulated by phylogenetic correlations across species in the location and number of introduction events. Main conclusions We demonstrate that the effects of anthropogenic introductions on the phylogenetic signal in range size vary across different stages in the invasion pathway. The process of transport and introduction amplifies the phylogenetic signal in the pool of potential invaders, whereas the subsequent pattern of spread decouples variation in alien range size from phylogenetic ancestry. Together, our findings suggest that evolutionary relatedness is likely to be a relatively weak predictor of the spread of invasive species.

Editorial - John Gilbert; Tim Phillips; Elke Anklam; Richard Stadler (Food Additives & Contaminants: Part A, 2018)

The potential global distribution of the brown marmorated stink bug, Halyomorpha halys, a critical threat to plant biosecurity - Darren J. Kriticos; John M. Kean; Craig B. Phillips; Senait D. Senay; Hernando Acosta; Tim Haye (Journal of Pest Science, 2017)

Land-use effects on local biodiversity in tropical forests vary between continents - Helen R. P. Phillips; Tim Newbold; Andy Purvis (Biodiversity and Conservation, 2017)

Expression of a fungal ferulic acid esterase in suspension cultures of tall fescue (Festuca arundinacea) decreases cell wall feruloylation and increases rates of cell wall digestion - Phillip Morris; Sue Dalton; Tim Langdon; Barbara Hauck; Marcia M. O. de Buanafina (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

A global analysis of the determinants of alien geographical range size in birds - Ellie E. Dyer; Victoria Franks; Phillip Cassey; Ben Collen; Robert C. Cope; Kate E. Jones; Çagan H. Şekercioğlu; Tim M. Blackburn (Global Ecology and Biogeography, 2016)
Aim Determining the causes of range size variation in the distributions of alien species is important for understanding the spread of invasive species. Factors influencing alien range size have been explored for some species at a regional level, but to date there has been no global analysis of an entire class. Here, we present such an analysis for birds, testing for the effects of introduction event, location and species‐level variables on alien range sizes. Location Global. Methods We used a novel dataset on the global distributions of alien bird species to test for relationships between alien range size and colonization pressure, residence time, extent of the global climatic niche, native range size, body mass and specialization, using a statistical approach based on phylogenetic generalized least squares models. We performed this analysis globally, and for separate biogeographical realms. Results Approximately half of the variation in alien bird range size is explained by colonization pressure in univariate analysis. We identified consistent effects of higher colonization pressure at global and realm levels, as well as support for effects of native range size and residence time. We found less support for effects of body mass, specialization or extent of the global climatic niche on alien range size. Main conclusions Alien bird range sizes are generally small relative to their native range sizes, and many are continuing to expand. Nevertheless, current variation is predictable, most strongly by the event‐level factor of colonization pressure. Whether a species is widespread is a better predictor of alien range size than whether a species could be widespread (estimated by global climatic niche extent), while we also find effects of residence time on alien range size. These relationships may help to identify those alien species that are more likely to spread and hence have greater environmental and economic impacts where they have been introduced.

On the island biogeography of aliens: a global analysis of the richness of plant and bird species on oceanic islands - Tim M. Blackburn; Steven Delean; Petr Pyšek; Phillip Cassey (Global Ecology and Biogeography, 2016)
Aim (1) To characterize the relationship(s) between species richness and area for alien plant and bird species on islands, and to identify commonalities and differences in those relationships for these different taxa, and between alien and native species; (2) to test whether area per se, native species richness or human factors related to area is the primary determinant of alien species richness; and (3) to explore the effects on alien island biogeography of isolation, productivity and the time since first European landfall. Location Islands around the world. Methods We used structural equation models ( SEMs ; supported by generalized linear models) to interrogate data on the alien and native species richness of birds and plants on islands. Results Alien plant and bird species richness were both strongly correlated with island area, with similar slopes on logarithmic axes. SEMs for both plants and birds revealed positive direct effects of native species richness and human population size, and positive indirect effects of area, on alien species richness. The models also identified indirect effects of temperature (positive) and isolation (negative) on alien species richness. Native plant and bird species richness were both predicted by direct effects of area (positive), temperature (positive) and isolation (negative). However, native plant richness was the only direct predictor of native bird species richness, and the strongest direct predictor of alien bird species richness, for islands with both plant and bird richness data. Main conclusions Our analyses recover the species–area, species–isolation and productivity relationships in native richness. Alien species richness was most strongly related to native species richness, with additional effects of human population size. Human population size most likely determines the number of alien species that arrive on an island, while the effect of native species richness may be driven by the influence of habitat heterogeneity on the likelihood that those populations persist (establishment success).

The wildlife pet trade as a driver of introduction and establishment in alien birds in Taiwan - Shan Su; Phillip Cassey; Tim M. Blackburn (Biological Invasions, 2016)

Long after the event, or four things we (should) know about bird invasions - Tim M. Blackburn; Ellie Dyer; Shan Su; Phillip Cassey (Journal of Ornithology, 2015)

Functional co-expression of a fungal ferulic acid esterase and a β-1,4 endoxylanase in Festuca arundinacea (tall fescue) modifies post-harvest cell wall deconstruction - Marcia M. de O. Buanafina; Sue Dalton; Tim Langdon; E. Timms-Taravella; Erica A. Shearer; Phillip Morris (Planta, 2015)

The influence of numbers on invasion success - Tim M. Blackburn; Julie L. Lockwood; Phillip Cassey (Molecular Ecology, 2015)
The process by which a species becomes a biological invader, at a location where it does not naturally occur, can be divided into a series of sequential stages (transport, introduction, establishment and spread). A species' success at passing through each of these stages depends, in a large part, on the number of individuals available to assist making each transition. Here, we review the evidence that numbers determine success at each stage of the invasion process and then discuss the likely mechanisms by which numbers affect success. We conclude that numbers of individuals affect transport and introduction by moderating the likelihood that abundant (and widespread) species are deliberately or accidentally translocated; affect establishment success by moderating the stochastic processes (demographic, environmental, genetic or Allee) to which small, introduced populations will be vulnerable; and affect invasive spread most likely because of persistent genetic effects determined by the numbers of individuals involved in the establishment phase. We finish by suggesting some further steps to advance our understanding of the influence of numbers on invasion success, particularly as they relate to the genetics of the process.

Plant characterization of Roundup Ready 2 Yield® soybean, MON 89788, for use in ecological risk assessment - Michael J. Horak; Eric W. Rosenbaum; Daniel L. Kendrick; Bernard Sammons; Samuel L. Phillips; Thomas E. Nickson; Raymond C. Dobert; Tim Perez (Transgenic Research, 2015)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

A population model for predicting the successful establishment of introduced bird species - Phillip Cassey; Thomas A. A. Prowse; Tim M. Blackburn (Oecologia, 2014)

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Propagule pressure as a driver of establishment success in deliberately introduced exotic species: fact or artefact? - Tim M. Blackburn; Thomas A. A. Prowse; Julie L. Lockwood; Phillip Cassey (Biological Invasions, 2013)

Expression of a Trichoderma reesei β-1,4 endo-xylanase in tall fescue modifies cell wall structure and digestibility and elicits pathogen defence responses - Marcia M. de O. Buanafina; Tim Langdon; Sue Dalton; Phillip Morris (Planta, 2012)

Establishment of exotic parasites: the origins and characteristics of an avian malaria community in an isolated island avifauna - John G. Ewen; Staffan Bensch; Tim M. Blackburn; Camille Bonneaud; Ruth Brown; Phillip Cassey; Rohan H. Clarke; Javier Pérez‐Tris (Ecology Letters, 2012)
Knowledge of the processes favouring the establishment of exotic parasites is poor. Herein, we test the characteristics of successful exotic parasites that have co‐established in the remote island archipelago of N ew Z ealand, due to the introduction of numerous avian host species. Our results show that avian malaria parasites ( AM ; parasites of the genus P lasmodium ) that successfully invaded are more globally generalist (both geographically widespread and with a broad taxonomic range of hosts) than AM parasites not co‐introduced to N ew Z ealand. Furthermore, the successful AM parasites are presently more prevalent in their native range than AM parasites found in the same native range but not co‐introduced to N ew Z ealand. This has resulted in an increased number and greater taxonomic diversity of AM parasites now in N ew Z ealand.

Passerine introductions to New Zealand support a positive effect of propagule pressure on establishment success - Tim M. Blackburn; Thomas A. A. Prowse; Julie L. Lockwood; Phillip Cassey (Biodiversity and Conservation, 2011)

Are compound leaves an adaptation to seasonal drought or to rapid growth? Evidence from the Amazon rain forest - Ana C. M. Malhado; Robert J. Whittaker; Yadvinder Malhi; Richard J. Ladle; Hans ter Steege; Oliver Phillips; L. E. O. C. Aragão; Timothy R. Baker; Luzmilla Arroyo; Samuel Almeida; Niro Higuchi; Tim J. Killeen; et al. (Global Ecology and Biogeography, 2010)
Aim To assess the hypotheses that compound leaves of trees in the Amazon forest are an adaptation to drought and/or rapid growth. Location Amazon rain forest, South America. Methods Genera from 137 permanent forest plots spread across Amazonia were classified into those with compound leaves and those with simple leaves. Metrics of compound leaf prevalence were then calculated for each plot and regression models that accounted for spatial autocorrelation were used to identify associations between climate variables and compound leaf structure. We also tested for associations between compound leaf structure and a variety of ecological variables related to life history and growth strategies, including wood density, annual increase in diameter and maximum height. Results One plant family, Fabaceae, accounts for 53% of compound‐leaved individuals in the dataset, and has a geographical distribution strongly centred on north‐east Amazonia. On exclusion of Fabaceae from the analysis we found no significant support for the seasonal drought hypothesis. However, we found evidence supporting the rapid growth hypothesis, with possession of compound leaves being associated with faster diameter growth rates and lower wood densities. Main conclusion This study provides evidence that possession of compound leaves constitutes one of a suite of traits and life‐history strategies that promote rapid growth in rain forest trees. Our findings highlight the importance of carefully considering the geographical distribution of dominant taxa and spatial clustering of data points when inferring ecological causation from environment–trait associations.

Elevation and habitats: the potential of sites at different altitudes to provide refuges for phytophagous insects during climatic fluctuations - Peter B. Hardy; Phillip M. Kinder; Tim H. Sparks; Roger L. H. Dennis (Journal of Insect Conservation, 2010)

The role of species traits in the establishment success of exotic birds - TIM M. BLACKBURN; PHILLIP CASSEY; JULIE L. LOCKWOOD (Global Change Biology, 2009)
There is now abundant evidence that propagule pressure, a composite measure of the number of individuals released into the nonnative location that varies between introduction events, is the most consistent predictor of success in the establishment of exotic species. However, the reasons why we expect propagule pressure to be important – because larger propagules ameliorate the effects of demographic, environmental or genetic stochasticity, or of Allee effects – also predict an influence of species traits on success. Here, we use a quantitative meta‐analytical approach to assess the effect of three categories of species‐level traits in the successful establishment of nonnative bird species: traits relating to population growth rates, traits that predispose species to Allee effects, and traits that enable a species to cope with novel environments. Traits that predispose species to Allee effects tend to decrease introduction success, whereas traits that enable a species to cope with novel environments tend to increase success. The breadth of habitats a species uses has the strongest mean effect of all variables analysed here. Mean effects for traits relating to population growth rates conflict in sign: in general, success is greater for species with large body mass whereas clutch size is not consistently related to establishment success. These results suggest a likely influence of some species‐level traits on exotic bird establishment success, especially traits that enable a species to cope with novel environments. We suggest that considering such traits in terms of the small‐population paradigm from conservation biology may be a productive avenue for future research.

The biogeography of avian extinctions on oceanic islands revisited - Tim M. Blackburn; Phillip Cassey; Karl L. Evans; Kevin J. Gaston; Richard P. Duncan (Journal of Biogeography, 2009)
A recent paper by Karels et al ., ‘The biogeography of avian extinctions on oceanic islands’ ( Journal of Biogeography , 2008, 35 , 1106–1111), uses structural equation modelling to assess the causes of the number of island bird species driven extinct in the historical period. Here, we critically assess the conclusions of the paper and argue that it does not provide the new insights into the causes of extinction in island birds that its authors claim.

Editorial - John Gilbert; Tim Phillips; Elke Anklam (Food Additives & Contaminants: Part A, 2009)

Geostatistical analysis of biomarkers of genotoxicity in cattle, Bos taurus and Bos taurus × Bos indicus, sentinels near industrial facilities - Wesley Bissett; Roger Smith; L. Garry Adams; Robert Field; William Moyer; Tim Phillips; H. Morgan Scott; James A. Thompson (Ecotoxicology, 2009)

Eggshell colour does not predict measures of maternal investment in eggs of Turdus thrushes - Phillip Cassey; John G. Ewen; Tim M. Blackburn; Mark E. Hauber; Misha Vorobyev; N. Justin Marshall (The Science of Nature, 2008)

The varying role of population abundance in structuring indices of biotic homogenization - Phillip Cassey; Julie L Lockwood; Julian D Olden; Tim M Blackburn (Journal of Biogeography, 2008)
Aim An important component of human‐induced global change is the decrease or increase in community distinctiveness (taxonomic homogenization or differentiation, respectively) that follows the loss of native species and gain of non‐native species. We use simulation approaches to assess the extent to which conclusions about the outcome of the homogenization process depend on whether or not abundance data are incorporated. Location Data were produced through computer simulation. Methods The frequency with which occurrence‐based similarity indices and abundance‐based similarity indices give different views of changes in community similarity, and the conditions under which such differences occurred were assessed using both deterministic and stochastic modelling approaches to simulate species assemblage states. Results Occurrence‐based and abundance‐based indices were positively correlated across the set of simulations for both the deterministic and stochastic models. However, in both situations approximately one quarter (25%) of models resulted in contrasting outcomes for the two approaches of calculating changes in compositional similarity; that is, one data type showed a positive value (homogenization), whereas the other showed a negative value (differentiation). Main conclusions In the majority of cases, species abundances will not change drastically enough after perturbation to produce large differences between homogenization scores measured using occurrence versus abundance information. However, in cases where these changes are large, it is important to recognize that the choice of metric to analyse homogenization trends will influence the qualitative and quantitative conclusions drawn. Studies of real assemblages are therefore necessary to evaluate the role of species abundance in defining the magnitude and direction of changes in community composition across space, and the implications of these changes for native biodiversity.

Threats to Avifauna on Oceanic Islands Revisited - TIM M. BLACKBURN; PHILLIP CASSEY; RICHARD P. DUNCAN; KARL L. EVANS; KEVIN J. GASTON (Conservation Biology, 2008)

The island biogeography of exotic bird species - Tim M. Blackburn; Phillip Cassey; Julie. L. Lockwood (Global Ecology and Biogeography, 2008)
Aim A recent upsurge of interest in the island biogeography of exotic species has followed from the argument that they may provide valuable information on the natural processes structuring island biotas. Here, we use data on the occurrence of exotic bird species across oceanic islands worldwide to demonstrate an alternative and previously untested hypothesis that these distributional patterns are a simple consequence of where humans have released such species, and hence of the number of species released. Location Islands around the world. Methods Statistical analysis of published information on the numbers of exotic bird species introduced to, and established on, islands around the world. Results Established exotic birds showed very similar species–area relationships to native species, but different species–isolation relationships. However, in both cases the relationship for established exotics simply mimicked that for the number of exotic bird species introduced. Exotic bird introductions scaled positively with human population size and island isolation, and islands that had seen more native species extinctions had had more exotic species released. Main conclusion The island biogeography of exotic birds is primarily a consequence of human, rather than natural, processes.

Origin, age, sex and breeding status of wandering albatrosses (Diomedea exulans), northern (Macronectes halli) and southern giant petrels (Macronectes giganteus) attending demersal longliners in Falkland Islands and Scotia Ridge waters, 2001–2005 - Helen Otley; Tim Reid; Richard Phillips; Andy Wood; Ben Phalan; Isaac Forster (Polar Biology, 2007)

HISTORICAL OBSERVATIONS OF HUMPBACK AND BLUE WHALES IN THE NORTH ATLANTIC OCEAN: CLUES TO MIGRATORY ROUTES AND POSSIBLY ADDITIONAL FEEDING GROUNDS - Randall R. Reeves; Tim D. Smith; Elizabeth A. Josephson; Phillip J. Clapham; Gillian Woolmer (Marine Mammal Science, 2004)
A bstract The seasonal distributions of humpback and blue whales ( Megaptera novaeangliae and Balaenoptera musculus , respectively) in the North Atlantic Ocean are not fully understood. Although humpbacks have been studied intensively in nearshore or coastal feeding and breeding areas, their migratory movements between these areas have been largely inferred. Blue whales have only been studied intensively along the north shore of the Gulf of St. Lawrence, and their seasonal occurrence and movements elsewhere in the North Atlantic are poorly known. We investigated the historical seasonal distributions of these two species using sighting and catch data extracted from American 18th and 19th century whaling logbooks. These data suggest that humpback whales migrated seasonally from low‐latitude calving/ breeding grounds over a protracted period, and that some of them traveled far offshore rather than following coastal routes. Also, at least some humpbacks apparently fed early in the summer west of the Mid‐Atlantic Ridge, well south of their known present‐day feeding grounds. In assessing the present status of the North Atlantic humpback population, it will be important to determine whether such offshore feeding does in fact occur. Blue whales were present across the southern half of the North Atlantic during the autumn and winter months, and farther north in spring and summer, but we had too few data points to support inferences about these whales' migratory timing and routes.

Variation in potential for isoprene emissions among Neotropical forest sites - Peter Harley; Pérola Vasconcellos; Lee Vierling; Carlos Cleomir de S. Pinheiro; James Greenberg; Alex Guenther; Lee Klinger; Samuel Soares de Almeida; David Neill; Tim Baker; Oliver Phillips; Yadvinder Malhi (Global Change Biology, 2004)
As part of the Large Scale Biosphere–Atmosphere Experiment in Amazônia (LBA), we have developed a bottom‐up approach for estimating canopy‐scale fluxes of isoprene. Estimating isoprene fluxes for a given forest ecosystem requires knowledge of foliar biomass, segregated by species, and the isoprene emission characteristics of the individual tree species comprising the forest. In this study, approximately 38% of 125 tree species examined at six sites in the Brazilian Amazon emitted isoprene. Given logistical difficulties and extremely high species diversity, it was possible to screen only a small percentage of tree species, and we propose a protocol for estimating the emission capacity of unmeasured taxa using a taxonomic approach, in which we assign to an unmeasured genus a value based on the percentage of genera within its plant family which have been shown to emit isoprene. Combining this information with data obtained from 14 tree censuses at four Neotropical forest sites, we have estimated the percentage of isoprene‐emitting biomass at each site. The relative contribution of each genus of tree is estimated as the basal area of all trees of that genus divided by the total basal area of the plot. Using this technique, the percentage of isoprene‐emitting biomass varied from 20% to 42% (mean=31%; SD=8%). Responses of isoprene emission to varying light and temperature, measured on a sun‐adapted leaf of mango ( Mangifera indica L.), suggest that existing algorithms developed for temperate species are adequate for tropical species as well. Incorporating these algorithms, estimates of isoprene‐emitting biomass, isoprene emission capacity, and site foliar biomass into a canopy flux model, canopy‐scale fluxes of isoprene were predicted and compared with the above‐canopy fluxes measured at two sites. Our bottom‐up approach overestimates fluxes by about 50%, but variations in measured fluxes between the two sites are largely explained by observed variation in the amount of isoprene‐emitting biomass.

Influences on the transport and establishment of exotic bird species: an analysis of the parrots (Psittaciformes) of the world - Phillip Cassey; Tim M. Blackburn; Gareth J. Russell; Kate E. Jones; Julie L. Lockwood (Global Change Biology, 2004)
Most studies of exotic species invasions only consider the factors that affect the establishment of populations following release, yet this is only one step on the invasion pathway. Different factors are likely to influence which species are transported and released. Here, we examine the influence of species traits on the successful transition of species through several stages in the introduction pathway (transport, release, and establishment), using parrots (Aves: Psittaciformes) as a model system. We use a species‐level supertree of parrots to test for phylogenetic auto‐correlation in the introduction process. Our analyses find that different sets of variables are related to the probability that a species enters each stage on the invasion pathway. The availability of individuals for transport and release seems to be most important for passage through these stages, but has no obvious effect on establishment following release. Rather, establishment success is higher for sedentary species, and species with broad diets.

The influence of spatial resolution on macroecological patterns of range size variation: a case study using parrots (Aves: Psittaciformes) of the world - Tim M. Blackburn; Kate E. Jones; Phillip Cassey; Neil Losin (Journal of Biogeography, 2004)
Aim To assess the extent to which the resolution at which geographical range sizes are measured influences macroecological patterns in this variable. Location Global. Methods Data on the geographical ranges of parrot species were digitized, and a Geographic Information System used to produce nine range size estimates for each species using different degrees of spatial resolution. The inter‐correlation of these estimates was then compared, together with their patterns of covariation with population size, body mass and migratory behaviour (across species and controlling for phylogeny), their pattern of phylogenetic correlation, and the frequency distributions of the different measures. Results Strong correlations exist among all nine range size measures across species, albeit that measures of similar spatial resolution are more strongly correlated. All measures show similar patterns of covariation with population size, body mass and migratory behaviour, and similar patterns of phylogenetic correlation. The skewness of frequency distributions increases towards zero as the resolution of the range size measure declines. Main conclusions The results of macroecological analyses are little affected by the resolution with which geographical range sizes are calculated, at least for the parrots of the world. Previously published studies based on crude measures of range size would be unlikely to have produced markedly different conclusions had they used more refined range size metrics.

Mistakes in the analysis of exotic species establishment: source pool designation and correlates of introduction success among parrots (Aves: Psittaciformes) of the world - Phillip Cassey; Tim M. Blackburn; Kate E. Jones; Julie L. Lockwood (Journal of Biogeography, 2004)
Aim To evaluate the effect of mis‐specifying the correct comparison of species pools in the study of species characteristics associated with the biological introduction of exotic species. Methods We use a high quality data set on biological introductions of parrots (Aves: Psittaciformes). These data allow us to examine relationships between life history traits and probability of successful transition through an introduction stage when the species pool is both correctly and incorrectly specified. Results For the establishment of introduced parrot species, nearly half of the predictor variables showed different patterns of significance when an incorrect pool was specified. Multivariate analysis identified entirely different sets of variables as independent predictors of establishment success, depending on the species pool used. Correct pool specification identified that introduced parrot species have been more likely to establish if they have broader diets and are more sedentary. Main conclusions Conclusions from the analysis of biological introductions are likely to depend on the specification of the species pool for such analyses. In the analysis of parrot introductions, this was particularly apparent in establishment success following release. Further studies that analyse the introduction pathway need to examine the effects of pool mis‐specification so that the generality of our results can be assessed.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)